Efficacy and Safety of Apixaban Compared With Warfarin in Patients With Atrial Fibrillation and Peripheral Artery Disease: Insights From the ARISTOTLE Trial - Peter T. Hu; Renato D. Lopes; Susanna R. Stevens; Lars Wallentin; Laine Thomas; John H. Alexander; Michael Hanna; Basil S. Lewis; Freek W. A. Verheugt; Christopher B. Granger; W. Schuyler Jones (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundWe studied (1) the rates of stroke or systemic embolism and bleeding in patients with atrial fibrillation and peripheral artery disease (PAD) and (2) the efficacy and safety of apixaban versus warfarin in patients with atrial fibrillation with and without PAD. Methods and ResultsThe Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (ARISTOTLE) trial randomized 18 201 patients with atrial fibrillation to apixaban or warfarin for stroke/systemic embolism prevention; 884 (4.9%) patients had PAD at baseline. Patients with PAD had higher unadjusted rates of stroke and systemic embolism (hazard ratio [HR] 1.73, 95% CI 1.22–2.45; P=0.002) and major bleeding (HR 1.34, 95% CI 1.00–1.81; P=0.05), but after adjustment, no differences existed in rates of stroke and systemic embolism (HR 1.32, 95% CI 0.93–1.88; P=0.12) and major bleeding (HR 1.03, 95% CI 0.76–1.40; P=0.83) compared with patients without PAD. The risk of stroke or systemic embolism was similar in patients assigned to apixaban and warfarin with PAD (HR 0.63, 95% CI 0.32–1.25) and without PAD (HR 0.80, 95% CI 0.66–0.96; interaction P=0.52). Patients with PAD did not have a statistically significant reduction in major or clinically relevant nonmajor bleeding with apixaban compared with warfarin (HR 1.05, 95% CI 0.69–1.58), whereas those without PAD had a statistically significant reduction (HR 0.65, 95% CI 0.58–0.73; interaction P=0.03). ConclusionsPatients with PAD in ARISTOTLE had a higher crude risk of stroke or systemic embolism compared with patients without PAD that was not present after adjustment. The benefits of apixaban versus warfarin for stroke and systemic embolism were similar in patients with and without PAD. These findings highlight the need to optimize the treatment of patients with atrial fibrillation and PAD. Clinical Trial RegistrationURL: http://www.clinicaltrials.gov. Unique identifier: NCT00412984.